David Hume's 'A Character of Sir Robert Walpole': Humean Factional Fears, the 'Rage against the Scots' and Future Historians. (October 2019) - Hanvelt, Marc; Spencer, Mark G.
Abstract : In this article we explore David Hume's essay of 1742, 'A Character of Sir Robert Walpole.' Modern scholars have not given this early, and admittedly minor, piece much attention. Hume's contemporaries did, and we find that it offers a surprisingly useful point of entry to larger concerns that engaged Hume throughout his career as a man of letters. In particular, the publishing history of Hume's 'Character' reveals significant developments in his thoughts on factionalism. Those developments become even more apparent when the essay and its revisions are put in context and read alongside other editorial decisions that Hume made about his Essays and Treaties and his History of England .